Comparative study between ultrasound findings and intra-operative findings in non-traumatic Abdominal Pain: - Gadban, Basim R. (Journal of the Faculty of Medicine Baghdad, 2012)
Background: acute abdominal pain is one of the most common presentations in surgical wards. Ultrasound has been grown in popularity as an easy, quick and non-invasive imaging the abdomen. US is very useful means of non-invasively, modality for assessment of acute abdominal pain.Objective: Study of the most common acute none traumatic abdominal diseases in adult patients admitted to Baghdad Teaching Hospital in department of surgery .Correlate the operative findings with sonographic features as to make the initial diagnosis of the diseases included in this study. Compare the diagnostic yield of abdominal ultrasound with that of computed tomography (CT).Methods :The present study included eighty nine consecutive adult patients with non traumatic abdominal pain as their chief complaint were admitted in the department of surgery at Baghdad Teaching Hospital during the period from April 2009 to January 2010.Ultrasound was performed in all patients in addition to CT scan as the first techniquesResults: The results showed that acute non traumatic abdominal pain was more frequently in female patients(73.46%) than male (26.53%).Gall bladder disease was the most common cause of upper abdominal surgeries (n= 45). No differences were observed between surgeries for intestinal obstruction or acute appendicitis(n=6) at P < 0.05 High accuracy of using of US, CT scan in the diagnosis of acute abdominal pain ,the compatibility with the operative finding was %89.79 , 83.33% respectively Conclusion: Sonography should be the first imaging technique in adult patients for the diagnosis of acute abdominal pain. CT scan should be used as a complementary study for suspected abdominal cases.